LEARNING & TEACHING PROBLEMS FOR SPECIAL SKILL CERTIFICATE DISABLED STUDENT (KHK) FOR HK COURSE 206 WESTERN FOOD PREPARATION (HEARING IMPAIRED CATEGORY) (Proceedings of International Conference on Special Education, 2015)
Students majoring in Certificate of Hotel & Catering Management in Tuanku Syed Sirajuddin Polytechnic, Perlis are disabled (Disabled People) with hearing impairment. They constitute a minority of students in Tuanku Syed Sirajuddin Polytechnic. The objective of this study is to help and find out the cause of the problems faced by disabled students, as well as suggestions on how to resolve the problems. This research is a quantitative research. Data was collected through questionnaires which were distributed during the class. The respondents were students of Hotel Management & Catering for semester 1 and 3, June 2013 session of the Department of Tourism and Hospitality. The results showed that the level of understanding and enjoyment of learning in the course is very low at 9%. Some of the proposed actions have been identified to improve student achievement in this subject.